Pengaruh likuiditas, profitabilitas,solvabilitas dan kualitas Auditor terhadap opini audit paragraph going concern pada perusahaan manufaktur sektor barang konsumsi yang terdaftar di bursa efek indondesia periode 2018-2020 - Rudy Hedianton Saragih; Bertha Elvy Napitupulu; Putri Febri Heryanti (Jurnal Ekonomi, Manajemen dan Akuntansi (JEKMA), 2022)
This study aimed to determine the influence of Liquidity, Profitability, Solvency, and Auditor Quality of Going Concern Paragraph Audit Opinion. The Population in this study was 58 Consumer Goods Manufacturing Companies listed in Indonesia Stock Exchange in 2018-2020. Sampling by using purposive sampling, in order to obtain 15 companies sampled for 3 years of observation (2018-2020), total data used in this study was 45. Data were analyzed using multiple logistic regression analysis. The results of this study showed the partially Liquidity, Profitability, Solvency, and Auditor Quality not has significant to the Going Concern Paragraph Audit Opinion. Whereas simultaneously with Omnibus Test of Model Coefficients, known Liquidity, Profitability, Solvency, and Auditor Quality significant effect to the Going Concern Paragraph Audit Opinion with a value significant of 0,004 which is less than 0,05.